Daylight Management in Mediterranean Cities: When Shortage Is Not the Issue - Judit Lopez-Besora; Glòria Serra-Coch; Helena Coch; Antonio Isalgue (Energies, 2016)
Natural resources such as daylight and sunlight are highly appreciated in countries with prevailing overcast skies. Taking advantage of this scarce resource contributes to saving energy on artificial lighting. In contrast to northern, southern European cities are distinguished by a large number of days with direct sunlight caused by a propitious climate condition. While it is a positive issue in terms of energy availability, the abundance of it can be counterproductive if management measures are not taken. Apart from the thermal consequences, lighting penetration into buildings causes a great contrast between inside and outside. This is especially critical when the visual system does not have enough time to adapt, as happens at entrance areas. The aim of this study is to analyze the light contrast between these areas and the urban outside in sunny conditions. To attain this objective, light data from five entrance spaces and their contiguous streets were analyzed and measured. The results were divided into three zones in the visual scene, showing an increasing contrast from top to bottom of the visual field. It may be concluded that interventions applied to urban areas and building pavements can improve visual adaptation in the transition zone.